Inteligencia emocional en estudiantes del grado sexto en la sede principal de la institución educativa José Ramón Bejarano en el Distrito de Buenaventura (2024)
The present study focused on evaluating the emotional intelligence (EI) of sixth grade students at the main headquarters of the José Ramón Bejarano Educational Institution in Buenaventura during the year 2024. The research was based on a descriptive quantitative design, using the TMMS-24 (Trait-Meta Mood Scale) instrument to evaluate Emotional Intelligence in a sample of 30 students between 12 and 14 years old. The target population was the sixth grade students of the José Ramón Bejarano Educational Institution in Buenaventura. A random sample of 30 students between 12 and 14 years of age were selected to participate in the study. The TMMS-24 instrument was used, based on the Trait-Meta Mood Scale (TMMS) of the Salovey and Mayer research group, adapted for adolescents. The TMMS-24 assesses five dimensions of EI: emotional self-awareness, emotional regulation, motivation, empathy, and social skills. The TMMS-24 was applied to the students in the sample individually and in person. The data obtained were analyzed using descriptive statistics to calculate measures of central tendency (mean) and dispersion (standard deviation) for each dimension of EI. The results of the study indicated that the sixth grade students of the José Ramón Bejarano Educational Institution presented average levels of emotional intelligence in all the dimensions evaluated. However, significant differences were observed in some dimensions, such as emotional self-awareness and motivation, between the different years of the study period. The present research provides valuable information about the emotional intelligence of sixth grade students at the José Ramón Bejarano Educational Institution. The results obtained can be used to design and implement intervention strategies that promote the development of EI in students, which could contribute to improving their emotional and academic well-being. It is recommended to conduct future research that expands the study sample to include students from other grades, educational levels and even from other schools in the Buenaventura District. It is also suggested to carry out longitudinal studies that allow analyzing the evolution of emotional intelligence over time.